Schizophyllum commune-induced allergic fungal rhinosinusitis and sinobronchial mycosis - Toshiaki Tsukatani (Medical Mycology Case Reports, 2015)
We present 32- and 38-year-old males with Schizophyllum commune-induced allergic fungal rhinosinusitis (AFRS). S. commune-induced AFRS was diagnosed by clinical and radiographic findings, positive specific IgE antibodies against S. commune as measured by the ImmunoCAP system, and sequencing analysis of the fungus. Our two cases with S. commune-induced AFRS for the first time showed evidence for type 1 hypersensitivity to S. commune as determined by using specific IgE antibodies against S. commune, and the fungus was identified by sequence analysis.